Enforcement Of The Law Against Defamation Crimes And Improvements Through Social Media Based On Law On Information And Transactions Electronics And Criminal Code - Laura Engellina Bri Siantur; Mutia Salsabila; Muhammad Fakar Ar-Ridho; M Sulthan Bakil Alrafif; Muhammad Fadl; Suci Ramadani (International Forum of Researchers and Lecturers, 2026)
Thei swifti advancementi ofi technologyi hasi madei iti simpleri fori individualsi toi accessi informationi viai sociali mediai platforms.i Nonetheless,i thisi cani alsoi leadi toi offenses,i includingi abusivei languagei ori expressionsi ofi animosityi towardsi othersi online.i Suchi actionsi falli underi Articlesi 310i andi 311i ofi thei Criminali Code,i whichi governi insultsi andi defamation,i alongi withi thei Informationi andi Electronici Transactionsi Lawi Numberi 11i Oct 2008.i Thisi lawi wasi revisedi toi includei Articlei 27i Paragraphi (3)i ini thei thei 2024i Informationi andi Electronici Transactionsi Law,i whichi tacklesi thei issuei ofi defamation.i Thei methodologyi appliedi ini thisi studyi isi normativei juridicali research,i emphasizingi ai legali approachi thati incorporatesi libraryi sources,i statutes,i regulations,i andi relevanti legali theoriesi andi concepts.i Thei obstaclesi ini applyingi thei lawi againsti defamationi crimesi oni sociali mediai encompassi legali issues,i technicali barriers,i andi culturali asi welli asi sociali factors.i Toi tacklei thesei obstacles,i i iti other essentiali toi enhancei thei skillsi ofi lawi enforcementi personneli andi boosti publici awarenessi abouti digitali literacy.i Thei processi ofi lawi enforcementi concerningi defamationi crimesi oni sociali mediai adheresi toi thei proceduresi outlinedi ini thei Criminali Procedurei Code,i focusingi oni electronici evidence.i Articlesi 310i andi 311i ofi thei Criminali Code,i togetheri withi Articlei 27i Paragraphi (3)i ofi thei Informationi andi Electronici Transactionsi Lawi asi amendedi ini Lawi Numberi 1i ofi 2024,i providei thei legali foundationi fori addressingi crimesi oni sociali media,i ini linei withi thei proceduresi seti forthi ini thei Criminali Procedurei Code.